The Impact of the Holy Qur'an on the Development of Cognitive Abilities (Journal of the College of Basic Education, 2026)
This research aims to shed light on the impact of the Holy Qur’an in shaping and developing human cognitive abilities. The Qur’an, being the final and everlasting divine scripture, was revealed as the ultimate guidance for humanity—reforming both worldly and spiritual affairs, It offers a foundation for knowledge, guides human understanding, distinguishes truth from falsehood, and fosters the advancement of life.In this study, I address the Qur’an’s emphasis on reflection, the use of reason, and the cultivation of understanding, as opposed to passive reception and blameworthy imitation. I examine various cognitive abilities as indicators of the Qur’an’s influence on the human mind, using a sample of students from Qur’an memorization centers as the study group.Five key cognitive abilities have been selected for evaluation: memorization, comprehension, perception, conviction, and recall.I ask Allah for sincerity, success, and benefit for both the writer and the reader.